Analisis Karakteristik Marshall pada Campuran Asphalt Concrete-Wearing Course (AC-WC) dengan Aspal Pen 60/70 Campur Serbuk Ban Karet - Fransiska Dona Artha; Gaffar Ali Akbar; Risdiyanto; Nur Ayu Diana (Faculty of Engineering, Widya Kartika University, 2026)
The Asphalt Concrete – Wearing Course (AC-WC) layer directly bears traffic loads, thus requiring high stability and durability. One of the efforts to improve the performance of the mixture while supporting the concept of sustainable construction is by utilizing rubber tire dust waste as an asphalt modifier. This study aims to determine the optimum asphalt content (KAO) and the optimum rubber content (KKO), as well as to analyze the effect of varying rubber tire dust content on Marshall characteristics. The research was conducted experimentally in the laboratory using the Marshall method according to the General Specifications of Bina Marga 2018. Variations in asphalt content for determining the KAO were 5%, 5.5%, 6%, 6.5%, and 7%. After obtaining the KAO, variations of rubber tire dust addition were made using the wet mixing method at 0%, 2%, 4%, 6%, and 8% by weight of asphalt. The parameters analyzed include stability, flow, Marshall Quotient (MQ), VITM, VFWA, and VMA. The addition of rubber tire dust improved stability and MQ, with the optimum values at a content of 4%, showing a stability of 1394 kg and an MQ of 449.68 kg/mm, which is about 24.6% higher than the mixture without rubber. However, at an 8% content, a decrease in VITM was observed to 2.78%, which is below the specification limit. The optimum rubber tire dust content of 4% significantly enhances Marshall characteristics and meets technical specifications, making it a promising alternative for stronger and more sustainable AC-WC mixtures.